2006
DOI: 10.1002/nbm.1034
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR spectroscopy for the prediction of therapeutic outcome in patients with fulminant hepatic failure

Abstract: A high-resolution (1)H NMR study of serum and urine of fulminant hepatic failure patients (n = 22) [surviving (n = 12) and non-surviving (n = 10)] is reported. Glutamine in serum and urine glutamine:creatinine ratio were higher in non-surviving patients compared with surviving patients [serum glutamine, 3.08 (1.68-7.11) vs 0.56 (0.34-0.99) mM, median and range; p = 0.0001 and urine glutamine:creatinine ratio, 1.72 (0.24-7.76) vs 0.39 (0.1-0.84), p = 0.1], and urine urea:creatinine ratio was higher in surviving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 21 publications
2
25
0
Order By: Relevance
“…ii) the enhancement of consumption of branched amino acids (BCAA), such as isoleucine, may characterize the inflammatory response in liver. Indeed, numerous studies have reported that the lactate is a major biomarker for tissue hypoxia and necrosis 29 and this fact could correspond to the inflammatory reaction and could lead to further increases in BCAA catabolism and glutamine production, consistent with the findings obtained in this study [30][31][32] .…”
Section: Discussionsupporting
confidence: 90%
“…ii) the enhancement of consumption of branched amino acids (BCAA), such as isoleucine, may characterize the inflammatory response in liver. Indeed, numerous studies have reported that the lactate is a major biomarker for tissue hypoxia and necrosis 29 and this fact could correspond to the inflammatory reaction and could lead to further increases in BCAA catabolism and glutamine production, consistent with the findings obtained in this study [30][31][32] .…”
Section: Discussionsupporting
confidence: 90%
“…A major challenge in the present practice of clinical medicine is the lack of suitable biomarkers and bioanalytical technologies for earlier detection of numerous diseases. Metabolic profiling or metabolomics, defined as the analysis of multiple biofluid metabolites in parallel, holds the promise of earlier disease detection and improved understanding of systems biology (1)(2)(3). Early indications of this potential have been reported for the detection of several diseases, including inborn errors of metabolism, cardiovascular diseases, and cancer (4)(5)(6)(7).…”
mentioning
confidence: 99%
“…Being the major organ for fatty acid metabolism and synthesis, liver graft failure results in lipid disturbance and a low circulation concentrations of fatty acids similar to thats observed in our patient. The liver is also the primary site of amino acid catabolism: an increase in circulating amino acids (e.g., tyrosine, glutamine, leucine) is reflective of hepatocyte injury and death (14,15). In our study, blood glutamine and methionine, two of the key compounds in liver nitrogen metabolism (11,15), as well as citrate were highly increased in the failed graft.…”
mentioning
confidence: 67%
“…Tests that measure hepatic function such as indocyanine green (ICG) (16) and lidocaine metabolism (15,17) are influenced by multiple factors and results are inconsistent. Blood metabolomics is a functional test that is able to monitor several metabolic pathways simultaneously (6).…”
mentioning
confidence: 99%